Problems of the Existence of Customary Institutions in Democratising Government in Negeri Abubu, Nusalaut District, Central Maluku Regency - Tanamal, Johan; Nahuway, Lodewyk (Journal of Law Science, 2024)
Indigenous Negeri-Negeri in local community governance today cannot be separated from efforts to adjust to the demands of democratisation and the principles of good and right governance. So that the goal of local community governance (Negeri) is the welfare of the Negeri community which has a strong local socio-cultural identity. This study aims to determine the root causes of the duties and functions of the Customary Institution (Saniri Negeri) in the democratisation of government in Negeri Abubu, Nusalaut sub-district, Central Maluku Regency. This type of research is qualitative research with data collection tools are observation, interviews and literature review. Determination of key informants was carried out after observation, then 9 informants were found who represented figures, women, community leaders, Soa heads, Saniri Negeri, religious leaders, youth leaders and the community. Furthermore, the data collected was then qualitatively analysed based on field reality through the following steps: data reduction, data testing and conclusion drawing. The results showed that the role of Saniri Negeri in carrying out the function of capturing the aspirations of the Abubu State Community has not been maximised, this action is evident where there has never been a meeting involving the Community in solving the problems faced by the Community, as well as in the process of aggregating aspirations has not gone well so that the draft State regulations that are determined are only the policies and knowledge of the Saniri Negeri body itself. So that the role of Saniri Negeri and the process of democratisation of government has not gone well.